Badan Pengawas Penyelidikan Kepolisian - Dahlil Marjon (Fakultas Hukum Universitas Mulawarman, 2009)
Conducting investigation to search for or to collect the evidence in confirming the crime committed, finding the suspect, revealing the suspect and the motive of crime, refer to some routine works of police officers. Investigation paradigms and concepts change from Holland colonial to recent age, which one seems related to the establishment of Investigation Supervisory Agency of Police Department. In term of philosophy, the establishment of this agency may be aimed to the public to control over investigator action during crime management and to regulate the police members in the investigation division into objective, proportional, and professional individual when they carry on the duty.